MEMBANGUN PERSAUDARAAN KRISTIANI MELALUI PAGUYUBAN KEMATIAN DI PAROKI MATER DEI MADIUN - Ronimus -; Cornelius Triwidya Tjahja Utama (Bahasa Indonesia, 2019)
A community is unity of people inspired by harmonious way of life inside of a group and organized system to achieve values of Christian Fraternity. However, thepeople in community itself often have not been able to comprehend values of Christian Fraternity. As a result, the dynamic community is only considered to fulfill its duties. This research applied qualitative method in order to answer some questions, such as what do you know about Christian fraternity? What are the aims of Christian fraternity according to you? What are the benefits of Christian Fraternity? What do you know about the community? What can you tell about the Death Community? What things have to be fulfilled by a member of Death Community? In your opinion, what are going to be built by PKPMD? Can you tell us how far PKPMD is trying to build up Christian fraternity? What are the obstacles which keep PKPMD from rising Christian fraternity? What do you expect from PKPMD in building up Christian fraternity? The result shows that three (50%) respondents interpreted Christian fraternity as fraternity in Christ. Four (66,7%) respondents thought that the aims of Christian fraternity are to raise togetherness based on affection. Three (50%) respondents stated that strengthening brotherhood is the benefit of Christian fraternity. Based on the analysis, three (50%) respondents construed that a community is a group of people which is cohesive in communication. Three (50%) respondents mentioned that having experience of cooperating with others in fraternity is typical of Death Community. Three (50%) said that expanding communication among people is a priority of PKPMD in rising Christian fraternity. Six (100%) respondents stated that the obstacle faced by PKPMD in building up Christian fraternity is the communication which has not been formed well. Three (50%) respondents said that PKPMD hopes to be able to work out closer cooperation for better communication.